Media, fake news and racismo:: the punitivism in rumors as a violence's legitimiser - Mendes Nunes Junior, Edson (2021)
This article aims to investigate the relation that exists between the propagation of fake news and the institutionalized racism in Brazil. We realized that the construction of the criminal’s image, associated to black people, relates to the destruction of the individual’s memory, seeking a violent act’s legitimation to restore an alleged ‘order’. Beyond a punitivist activity in the mainstream media, there is a non-official form of media that acts in the social media that, as an expression of the dominant ideology in society, creates rumors to justify excesses and violence against blacks and poor people in a systematic way. Authors as Evgeni Pachukanis, Loic Wacquant and Marielle Franco helps us to iniciate a discussion about Criminal Law, criminal State and peripherals bodies and spaces ‘militarization’. Finally, we present some concrete cases that allow us to notice a continuous action, in the same modus operandis, regarding the destruction of black and marginalized victims of violence’s memory.